2012
DOI: 10.5114/pdia.2012.32386
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer in the elderly – epidemiological, clinical and surgical treatment analysis of 254 patients

Abstract: A b s t r a c t I In nt tr ro od du uc ct ti io on n: : The incidence of non-melanoma skin cancer (NMSC) and melanoma is increasing rapidly in the European population. There are only a few reports about cutaneous malignancy in the elderly population. A Ai im m: : Epidemiological, clinical, histopathological and surgical treatment result analysis of skin cancers in patients over 75 years old. M Ma at te er ri ia al l a an nd d m me et th ho od ds s: : A group of 254 patients over 75 years old operated on during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…BCCs are more common in the elderly age group. In recent years, the incidence rate has increased significantly in younger patients and in females according to De Vries et al [11] and Sobjanek et al [12] Most common age group in our study is less than 60 years (60%) followed by > 60 years (40%). This closely resembles the findings in a study in North India.…”
Section: Discussionsupporting
confidence: 66%
“…BCCs are more common in the elderly age group. In recent years, the incidence rate has increased significantly in younger patients and in females according to De Vries et al [11] and Sobjanek et al [12] Most common age group in our study is less than 60 years (60%) followed by > 60 years (40%). This closely resembles the findings in a study in North India.…”
Section: Discussionsupporting
confidence: 66%
“…Approximately 75–80% of cases of NMSC refer to BCC, which is diagnosed in 800,000 patients annually in the USA; although BCC is typical in elderly subjects, its average age of onset is constantly decreasing. Polish research has revealed that cutaneous malignancies have become more common in the Polish population over recent decades . The present research reports the occurrence of malignant skin neoplasms in 17.7% of examined patients.…”
Section: Discussionmentioning
confidence: 55%
“…Polish research has revealed that cutaneous malignancies have become more common in the Polish population over recent decades. 34 The present research reports the occurrence of malignant skin neoplasms in 17.7% of examined patients. Remarkably, 85.7% of these malignancies were diagnosed in patients hospitalized on the dermatology ward, which emphasizes the fact that cutaneous malignancies are a common reason for admission to dermatology departments in elderly patients.…”
Section: Discussionmentioning
confidence: 68%
“…At diagnosis, most patients are in their sixth and seventh decade of life and men are twice as likely to develop BCC. The incidence of BCC has tripled in the last 30 years (Staples et al 2006 ) and, in recent years, the incidence rate has increased significantly in younger patients and in females (De Vries et al 2004 ; Sobjanek et al 2012 ) due to the increasing use of artificial sources of ultraviolet radiation (UVR), primarily solar beds (Werher et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%